STUDI KUALITATIF PERAN PETUGAS KESEHATAN DAN KADER DESA DALAM PROGRAM PENGOBATAN MASSAL FILARIASIS DI KABUPATEN MAMUJU UTARA PROVINSI SULAWESI BARAT TAHUN 2015 - Made Agus Nurjana; Hayani Anastasia; Rosmini Rosmini; Sitti Chadijah; Mujiyanto Mujiyanto; Ni Nyoman Veridiana; Octaviani Octaviani; Leonardo Taruk Lobo (SPIRAKEL, 2018)
The role of health workers and health volunteer are essential in the implementation of mass drug administration (MDA) in North Mamuju District. Several activities were conducted prior MDA, such as advocacy to policy makers (e.g regent) and socialization from district level to village level. Qualitative research methods and datacollection were carried out for six months. Interviewed to 17 health workers and 60 health volunteers were conducted by using an open questionnaire, which aimed to know the role of each health workers and health volunteers in the implementation of MDA for the last two years. The study result showed that the role of health workers and health volunteers was not fully optimised because the lack of budget and human resource. Therefore, to optimise the role of health workers and health volunteers, the authority needs to consider to allocate a sufficient budget and human resource for the implementation of MDA